Perkembangan Ekspor Crude Palm Oil (CPO) Indonesia menuju Tiongkok (Implementasi ASEAN-China Free Trade Area) - Apriolla Azzahra; Grea Agustin; Melissa Surya; Reni Marlina (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study examines the development of Indonesian Crude Palm Oil (CPO) exports to China, particularly after the implementation of the ASEAN-China Free Trade Area (ACFTA) since 2010. Using a descriptive qualitative method with literature studies and secondary data analysis from the Central Statistics Agency, this study assesses the impact of ACFTA on the increase in the volume and value of Indonesian CPO exports. The results show that the elimination of more than 94% of tariffs on palm oil products has increased market access and strengthened the competitiveness of CPO products in China, resulting in a continuous increase in export volume, even though export value has been affected by fluctuations in global market prices. The study also identifies factors supporting export growth, such as China's economic and demographic conditions and the trade policies of both countries. On the other hand, Indonesian CPO exports face obstacles in the form of strict quality standards related to free fatty acids, heavy metals, and pesticides, as well as environmental sustainability challenges due to issues of deforestation and land use change. The need to comply with NDPE (No Deforestation, No Peat, No Exploitation) principles requires businesses to improve transparency and obtain appropriate certification. In addition, the uneven institutional capacity to access certification is an obstacle that needs to be overcome. In conclusion, Indonesia's CPO exports to China have grown significantly thanks to the influence of ACFTA and economic factors, but improvements are still needed in terms of quality, sustainability, and trade diplomacy in order to maintain competitiveness and optimize opportunities in this highly demanding global market. Efforts to improve regulations and industrial efficiency are essential for Indonesia to remain a leading palm oil producer in the world.